Exploring the recovery of a large wetland using black‐necked swan blood parameters and body condition 16 years after a pollution‐induced disturbance. (17th March 2023) - Rodríguez‐Jorquera, Ignacio A.; Lenzi, Javier; Maturana, Mario; Biscarra, Gabriela; Ruiz, Jorge; Navedo, Juan G.
Abstract: Resilience theory has taken center stage in tackling the challenge of wetland recovery on a fast‐changing planet. Because of waterbirds' enormous dependence on wetlands, their numbers have long been used as surrogates for wetland recovery over time. However, immigration of individuals can mask actual recoveries at a given wetland. One alternative to expanding the knowledge of wetland recovery is the use of physiological parameters from aquatic organism populations. We explored the variations in the physiological parameters of black‐necked swan (BNS) before, during, and after a 16‐year period of a pollution‐induced disturbance that originated in a pulp‐mill wastewater discharge. This disturbance triggered the precipitation of iron (Fe) in the water column of the Río Cruces Wetland in southern Chile, one of the main sites for the global population of BNS Cygnus melancoryphus . We compared our recent (2019) original data (body mass index [BMI], hematocrit, hemoglobin, mean corpuscular volume, blood enzymes, and metabolites) with available datasets from the site obtained before the pollution‐induced disturbance (2003) and immediately after the disturbance (2004). Results indicate that, 16 years after the pollution‐induced disturbance, some important parameters of animal physiology did not return to their pre‐disturbance state. For instance, BMI, triglycerides, and glucose were significantly higher in 2019 than in 2004, right after the disturbance. By contrast, the hemoglobin concentration was significantly lower in 2019 than in 2003 and 2004, and uric acid was 42% higher in 2019 than in 2004. Our results demonstrate that, despite higher BNS numbers with larger body weights present in 2019, the Río Cruces wetland has only partially recovered. We suggest that the impact of megadrought and wetland disappearance far from the site results in high rate of swan immigration, casting uncertainty about using the number of swans alone as honest indicators of wetland recovery after a pollution disturbance. Integr Environ Assess Manag 2023;19:663–675. © 2023 SETAC Key Points: Sixteen years after a pollution disturbance, the number of black‐necked swans (BNS) is greater, with higher body weights but with poorer blood parameters, casting uncertainty about the use of bird abundance alone as an honest indicator of wetland recovery. Black‐necked swan body mass index, triglycerides, and glucose were higher than normal after the perturbation; by contrast, hemoglobin concentration was significantly lower and uric acid was 42% higher, and all these findings can be related to oxidative stress. Despite higher food availability, hematological and biochemical parameters suggest long‐term reduction in BNS general health status; thus, the effects of wetland concentrations of iron need to be investigated because Fe overload exerts oxidative stress and alters Fe cellular homeodynamics. Long‐term impacts of pollution on waterbird body condition, physiology, and fitness should better be used as input for wetland recovery assessment, considering broader temporal and geographical scales to track wetland resilience.